Metamorphoses of Over a Hundred Years of Research on the Artistic Legacy of the Kłodzko Jesuits (Prologue to the Full Catalogue of Kłodzko Design Drawings from the 17th and 18th Centuries) (Theatrum historiae, 2025)
The overview article outlines 140 years of research into the Baroque art of the Kłodzko Jesuits. It remained in close connection with the activities in the towns and villages near Kłodzko, belonging to the post-war aristocracy, among whom were many of the donors of the Kłodzko college. This art was insufficiently perceived in the context of the rest of Bohemia, and after World War II, it even weighed on the work of Polish art historians the ahistorical, even absurd paradigm of “Silesian Kłodzko.” Over the past 30 years or so, it is continuously being broken through. However, there is still little interest in the Kłodzko Baroque from Czech researchers. Meanwhile, a still little-studied phenomenon of this art is the existence of a collection of more than 200 design drawings from the 17th-18th centuries that were left by the Jesuits (including works by Simon Pitz and Carlo Lurago). This set was scattered after 1945. The larger part is in the archives of the Jesuits in Kraków, while a smaller and only recently discovered one is in the rectory of the parish church in Kłodzko. Both of these sets should be comprehensively compiled, first of all, in the form of a scientific catalogue, especially since its separation is completely artificial and haphazard; moreover, the Kłodzko set remains uninventoried (the drawings lack signatures), and the whole represents Bohemian (Czech) cultural heritage beyond the borders of Czechia.
Keywords: Kłodzko; Jesuits; Art; Baroque; Historiography; Design Drawings; Carlo Lurago